Trends in incidence of youth-onset type 1 and type 2 diabetes in the USA, 2002–18: results from the population-based SEARCH for Diabetes in Youth study. Issue 4 (April 2023) - Wagenknecht, Lynne E; Lawrence, Jean M; Isom, Scott; Jensen, Elizabeth T; Dabelea, Dana; Liese, Angela D; Dolan, Lawrence M; Shah, Amy S; Bellatorre, Anna; Sauder, Katherine; Marcovina, Santica; Reynolds, Kristi; et al.
Summary: Background: The incidence of diabetes is increasing in children and young people. We aimed to describe the incidence of type 1 and type 2 diabetes in children and young people aged younger than 20 years over a 17-year period. Methods: The SEARCH for Diabetes in Youth study identified children and young people aged 0–19 years with a physician diagnosis of type 1 or type 2 diabetes at five centres in the USA between 2002 and 2018. Eligible participants included non-military and non-institutionalised individuals who resided in one of the study areas at the time of diagnosis. The number of children and young people at risk of diabetes was obtained from the census or health plan member counts. Generalised autoregressive moving average models were used to examine trends, and data are presented as incidence of type 1 diabetes per 100 000 children and young people younger than 20 years and incidence of type 2 diabetes per 100 000 children and young people aged between 10 years and younger than 20 years across categories of age, sex, race or ethnicity, geographical region, and month or season of diagnosis. Findings: We identified 18 169 children and young people aged 0–19 years with type 1 diabetes in 85 million person-years and 5293 children and young people aged 10–19 years with type 2 diabetes in 44 million person-years. In 2017–18, the annual incidence of type 1 diabetes was 22·2 per 100 000 and that of type 2 diabetes was 17·9 per 100 000. The model for trend captured both a linear effect and a moving-average effect, with a significant increasing (annual) linear effect for both type 1 diabetes (2·02% [95% CI 1·54–2·49]) and type 2 diabetes (5·31% [4·46–6·17]). Children and young people from racial and ethnic minority groups such as non-Hispanic Black and Hispanic children and young people had greater increases in incidence for both types of diabetes. Peak age at diagnosis was 10 years (95% CI 8–11) for type 1 diabetes and 16 years (16–17) for type 2 diabetes. Season was significant for type 1 diabetes (p=0·0062) and type 2 diabetes (p=0·0006), with a January peak in diagnoses of type 1 diabetes and an August peak in diagnoses of type 2 diabetes. Interpretation: The increasing incidence of type 1 and type 2 diabetes in children and young people in the USA will result in an expanding population of young adults at risk of developing early complications of diabetes whose health-care needs will exceed those of their peers. Findings regarding age and season of diagnosis will inform focused prevention efforts. Funding: US Centers for Disease Control and Prevention and US National Institutes of Health.